2007
DOI: 10.1080/03630260601057104
|View full text |Cite
|
Sign up to set email alerts
|

Study of β-Thalassemia Mutations Using the Polymerase Chain Reaction-Amplification Refractory Mutation System and Direct DNA Sequencing Techniques in a Group of Egyptian Thalassemia Patients

Abstract: The aim of this study was the molecular characterization of beta-thalassemia (thal) mutations in a group of 95 Egyptian thalassemic patients from Fayoum in Upper Egypt, Cairo, Alexandria and Tanta in Lower Egypt and the Nile Delta. To identify these anomalies, the polymerase chain reaction-amplification refractory mutation system (PCR-ARMS) technique was used, complemented by direct DNA sequencing for uncharacterized cases. In 80 of the 95 patients, the beta-thal mutation was detected by PCR-ARMS. The most com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 11 publications
2
10
0
Order By: Relevance
“…A recent study of 95 Egyptian betathalassemic cases illustrated that the three most common HBB mutations observed were at c.92+6 (36.3%), c.93-21 (25.8%), and c.92+1 (19.0%) [53], similar to the findings in other studies carried out on Egyptians [54][55][56] (Table 2). Moreover, the seven most frequent alleles in this study accounted for 84.2% of the observed thalassemic alleles in Egypt.…”
Section: Prevalence Of Beta-thalassemia Throughout the Middle Eastsupporting
confidence: 86%
“…A recent study of 95 Egyptian betathalassemic cases illustrated that the three most common HBB mutations observed were at c.92+6 (36.3%), c.93-21 (25.8%), and c.92+1 (19.0%) [53], similar to the findings in other studies carried out on Egyptians [54][55][56] (Table 2). Moreover, the seven most frequent alleles in this study accounted for 84.2% of the observed thalassemic alleles in Egypt.…”
Section: Prevalence Of Beta-thalassemia Throughout the Middle Eastsupporting
confidence: 86%
“…For RDB, a panel of primers and probes (n=22) using the β-globin strip assay was used (β-Globin Strip Assay MED kit, VIENNA LAB, REF. 4-130) [14].…”
Section: Methodsmentioning
confidence: 99%
“…ElGawhary et al, (2007) reported that IVSI-6 is more frequent than IVSI-110, but their study covered Fayoum in Upper Egypt, Cairo, Alexandria and Tanta in Lower Egypt and the Nile Delta. The proportion of IVS-I-6 (T→C) was 36.30% and that of IVSI-110 (G→A) was 25.8% [20].…”
Section: β-Globin Gene Mutation By Allele Specific Pcrmentioning
confidence: 92%